Pengaruh Pertumbuhan Ekonomi, Investasi Dan Kualitas Manusia Dalam Menurunkan Kemiskinan Di Indonesia - Azizah, Nur; Astuty, Sri; Jamil, Muh.; Rajab, Abdul (Jurnal EMT KITA, 2026)
Poverty remains a structural issue in Indonesia. This study aims to examine the effects of economic growth, investment, and human capital on poverty in Indonesia. The study employs panel data from 33 provinces over the period 2010–2023, obtained from official government sources. The analytical method used is multiple linear regression under the Common Effect Model (CEM) as the preferred estimation model, combined with Driscoll–Kraay robust standard errors to ensure stable and reliable estimates. This approach allows for testing both the partial and simultaneous effects of the independent variables on poverty. The findings indicate that economic growth has a positive and statistically significant effect on poverty, suggesting that growth during the study period has not been fully inclusive and tends to be capital-intensive in nature. In contrast, investment and human capital exhibit negative and statistically significant effects on poverty, implying that both factors contribute to reducing the number of poor individuals. Simultaneously, all independent variables are jointly significant, with a coefficient of determination of 70.23 percent. This study concludes that poverty alleviation strategies should not rely solely on economic growth but must also prioritize productive investment and human capital development in order to achieve inclusive and equitable development.